PENGEMBANGAN DAN POLA PEMBINAAN INDUSTRI KREATIF ‘SONGKOK RECCA’ DESA PACCING KABUPATEN BONE - Sumantri, Dody Syam; Faisal, Muh (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2023)
The main problem in this research is how the development and pattern of fostering the Songkok Recca creative industry in Paccing Village, Awangpone District, Bone Regency. This study aims to determine the development of the Songkok Recca creative industry in Paccing Village, Awangpone District, Bone Regency and to determine the patterns of fostering and regenerating the Songkok Recca creative industry in Paccing Village, Awangpone District, Bone Regency. The method used in this research is descriptive qualitative method.The subjects in this research were craftsmen who had decades of experience and Songkok Recca entrepreneurs who had also carried out their activities for many years. This research data was obtained through observation techniques, interviews and documentation which were used to obtain concrete data related to this research problem.The results of this research show the development and pattern of fostering the Songkok Recca creative industry in Paccing village, Awangpone District, Bone Regency. Songkok Recca has undergone various developments, including developing motifs, developing shapes and developing the materials used. Likewise, the development of marketing for Songkok Recca productionIt has spread to overseas countries such as Australia and Malaysia. For training patterns for craftsmen carried out in the form of divisions. There are those that are built specifically to make just the base part, there are those that are built specifically to make only the surrounding parts and there are also those that are built to make from the base to the end a Songkok Recca. Furthermore, for regeneration training, the craftsmen hold training and training within their respective families which is intended as the next generation of their creative industry efforts so that the Songkok Recca creative industry in Paccing village, Awangpone subdistrict, Bone Regency continues to develop and be sustainable.